Astaxanthin degradation and lipid oxidation of Pacific white shrimp oil: kinetics study and stability as affected by storage conditions - Takeungwongtrakul, Sirima; Benjakul, Soottawat (My University, 2016)
The kinetics of astaxanthin degradation and lipid oxidation in shrimp oil from hepatopancreas of Pacific white shrimp (Litopenaeus vannamei) as affected by storage temperature were studied. When shrimp oil was incubated at different temperatures (4, 30, 45 and 60 °C) for 16 h, the rate constants (k) of astaxanthin degradation and lipid oxidation in shrimp oil increased with increasing temperatures (p < 0.05). Thus, astaxanthin degradation and lipid oxidation in shrimp oil were augmented at high temperature. When shrimp oils with different storage conditions (illumination, oxygen availability and temperature) were stored for up to 40 days, astaxanthin contents in all samples decreased throughout storage (p < 0.05). All factors were able to enhance astaxanthin degradation during 40 days of storage. With increasing storage time, the progressive formation of primary and secondary oxidation products were found in all samples as evidenced by the increases in both peroxide values (PV) and thiobarbituric acid reactive substances (TBARS) (p < 0.05). Light, air and temperatures therefore had the marked effect on astaxanthin degradation and lipid oxidation in shrimp oils during the extended storage.
Keywords: Astaxanthin degradation; Illumination; Lipid oxidation; Oxygen availability; Shrimp oil; Temperature